Taking stock of alma-ata primary health care/health for all: moving toward new directions in global preventive health - Wong, Y.L. (SAGE Publications, 2011)
Health for All by 2000,first declared at Alma-Ata in 1978, revolutionized primary health care (PHC) policy and planning based on a set of guiding values and principles of health services organization: equity, social justice, and health for all; community participation; appropriate use of resources; and intersectoral action. Primarily, the historic significance of the Alma-Ata/Health for All (HFA) was to put preventive health on equal footing as curative medicine.